Ownership structure and asset sales: An empirical analysis - Michael J. Bennett (Queen's University, Department of Economics, 2004)
This paper examines the effect of ownership structure on the market assessment of asset sales. Three types of ownership structures are identified: large block outside, inside, and widely held. Empirical results indicate that firms with large block outside shareholders experience significantly positive announcement effects for both buying and selling firm samples. These are significantly greater than those for the inside shareholder and large widely held firms. Two other questions are examined. For the second question, the sample is partitioned in a pair wise way to see if the ownership structure of the firm being transacted with has an effect. Results suggest that the ownership structure of the firm on the other side of the deal does have an effect The third question examines whether ownership has an effect in the presence of other types of information, specifically, the release of the price paid for the asset. In the presence of an ownership variable, the disclosure of price does not have an effect on the market's reaction to the asset sale.
Keywords: G32; G34; G38; 330; Ownership Structure; Asset Sales; Market Valuation